2018
DOI: 10.1016/j.pt.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Gut Microbiota and Common Luminal Intestinal Parasites

Abstract: The development and integration of DNA-based methods in research and clinical microbiology laboratories have enabled standardised and comprehensive detection and differentiation of the microbes colonising our guts. For instance, the single-celled parasites Blastocystis and Dientamoeba appear to be much more common than previously thought, especially so in healthy individuals. While increasing evidence appears to suggest limited pathogenicity of these parasites, next-generation-sequencing-based studies have hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
144
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 94 publications
5
144
0
1
Order By: Relevance
“…Other EPs such as the heterokont Blastocystis sp. and the protozoan Dientamoeba fragilis appear much more common than previously thought, especially in healthy individuals [1113] and have been associated with gastrointestinal disorders including irritable bowel syndrome [14]. Because of its high degree of genetic diversity, a total of 17 subtypes (STs) with marked differences in host specificity and geographical distribution have been recognised within Blastocystis , with STs 1–4 accounting for ~90% of the human infections reported globally [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other EPs such as the heterokont Blastocystis sp. and the protozoan Dientamoeba fragilis appear much more common than previously thought, especially in healthy individuals [1113] and have been associated with gastrointestinal disorders including irritable bowel syndrome [14]. Because of its high degree of genetic diversity, a total of 17 subtypes (STs) with marked differences in host specificity and geographical distribution have been recognised within Blastocystis , with STs 1–4 accounting for ~90% of the human infections reported globally [15].…”
Section: Introductionmentioning
confidence: 99%
“…The GI tract is a complex environment where host, pathogen and microbiota interact to affect disease pathogenesis 9 . We previously demonstrated that T. cruzi infection affects the fecal microbiome and metabolome, but information on the specific GI sites driving this output had not yet been determined 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no exclusively eukaryotic microbiota transplants (single or a few microbes introduced into a host are better described as probiotics), there has been a little attention to how eukaryotic microbes work in FMT treatments. Some of the existing scrutiny is negative: if Blastocystis and other protists are found in donor stools for FMTs, that stool sample is often excluded from the treatment (Stensvold and van der Giezen ). Fungal contributions to general FMTs are just beginning to be assessed.…”
Section: Comparing Bacterial and Eukaryotic Gut Microbiome Research Smentioning
confidence: 99%
“…). Correlations between Blastocystis and anaerobic bacteria can also be driven by oxygen levels (Stensvold and van der Giezen ) and require particular age‐related diversity conditions in the bacterial gut microbiota (Scanlan et al. ).…”
Section: Cross‐domain Relationships and Their Implicationsmentioning
confidence: 99%